2020
DOI: 10.1016/j.ebiom.2020.102955
|View full text |Cite
|
Sign up to set email alerts
|

N6-Methyladenosine modification of the TRIM7 positively regulates tumorigenesis and chemoresistance in osteosarcoma through ubiquitination of BRMS1

Abstract: Background Metastasis is the leading cause of death in patients with osteosarcoma. Some of these patients fail to respond to chemotherapy and die of metastasis within a short period. Therefore, it is important to identify novel biomarkers to improve the diagnosis and treatment of osteosarcoma. TRIM7 is a member of the tripartite motif (TRIM) family protein that is involved in various pathological conditions including cancer; however, its role in osteosarcoma remains elusive. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
67
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(71 citation statements)
references
References 45 publications
4
67
0
Order By: Relevance
“…METTL3/14 also plays an important role in modulating the chemoresistance of osteosarcoma. METTL3 and METTL14 decrease the RNA level of tripartite motif 7 (TRIM7), while the upregulation of TRIM7 can increase metastasis and the chemoresistance of osteosarcoma by regulating ubiquitination of breast cancer metastasis suppressor 1 (BRMS1) (69). The transcriptome-wide m 6 A sequencing result of chemoresistant osteosarcoma stem cells revealed that over-expression of METTL3 and low METTL14 expression are associated with doxorubicin chemoresistance and stemness of osteosarcoma cells (70).…”
Section: Dysregulation Of M 6 a Writers In Osteosarcomamentioning
confidence: 99%
See 3 more Smart Citations
“…METTL3/14 also plays an important role in modulating the chemoresistance of osteosarcoma. METTL3 and METTL14 decrease the RNA level of tripartite motif 7 (TRIM7), while the upregulation of TRIM7 can increase metastasis and the chemoresistance of osteosarcoma by regulating ubiquitination of breast cancer metastasis suppressor 1 (BRMS1) (69). The transcriptome-wide m 6 A sequencing result of chemoresistant osteosarcoma stem cells revealed that over-expression of METTL3 and low METTL14 expression are associated with doxorubicin chemoresistance and stemness of osteosarcoma cells (70).…”
Section: Dysregulation Of M 6 a Writers In Osteosarcomamentioning
confidence: 99%
“…Additionally, HNRNPC and HNRNPA2B1 are found only in the nucleus (63). YTHDF2 can directly bind to the 3'-UTR of TRIM7 mRNA and negatively regulate the expression of TRIM7 in osteosarcoma HOS and MG63 cells (69). ELAVL1 (also known as HuR) is a recently discovered m 6 A reader, which is located in the nucleus.…”
Section: Dysregulation Of M 6 a Readers In Osteosarcomamentioning
confidence: 99%
See 2 more Smart Citations
“… 28 The aberrant m 6 A modifications mediated by FTO expression contributed to the development of cancers. 29–31 m 6 A RNA methylation regulators are crucial participants in the malignant progression of CNS tumor. FTO may preferentially mediate demethylation of different methylation targets in CNS tumor.…”
Section: Introductionmentioning
confidence: 99%